Urgensi Pendidikan Ham sebagai Metode Khittah Etika Moralitas dalam Dunia Pendidikan - Muhammad Hafidz Khusnadin; Muhammad Suyatno; Ilma Maulana Ahmad; Ahmad Zumaro (Jurnal Syntax Admiration, 2025)
The development of the times and the increasingly massive globalization provide their own challenges to ethical values and morality. The world of education often faces situations and conditions where norms intersect with universal values, such as human rights. Education bears the responsibility to realize the realization of human rights, such as freedom of expression, creativity, freedom to obtain information and proper education, and so on. Education, as its function is the transfer of value, instills human values so that no deviations or violations occur. Education is the last hope for the process of internalizing human rights values. The method used in this research is descriptive-qualitative with a normative-historical approach. This article is a library research by searching for data through literature review, which is a series of activities related to the methods used in collecting library data. The results of this study explain that human rights education has an important role in building the mindset and creating the character of academics with integrity. In addition, human rights education is also important as a method of ethical morality in the midst of the times. Along with the progress of the times and the increasingly massive technological developments, human rights education is needed as an instrument to strengthen individual awareness of fundamental rights and universal norms so that ethical morality is maintained and not eroded due to globalization.